2020
DOI: 10.1111/ajco.13454
|View full text |Cite
|
Sign up to set email alerts
|

Real‐world efficacy and safety of immune checkpoint inhibitors in advanced hepatocellular carcinoma: Experience of a tertiary Asian Center

Abstract: Introduction: Immune checkpoint inhibitor (ICI) use in advanced hepatocellular carcinoma (HCC) is increasing. Real-world data on efficacy and safety, however, are lacking. Methods:We conducted a retrospective review of all patients with advanced HCC seen at our center who received at least one dose of an ICI between May 2015 and June 2018. Data cutoff was December 31, 2018. Responses were evaluated using Response Evaluation Criteria in Solid Tumors version 1.1 criteria. Results:Of 114 patients, 88.6% were male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 29 publications
1
36
0
Order By: Relevance
“…OncoTargets and Therapy 2020:13 prognosis remains poor and the rate of irAEs always higher than patients with Child-Pugh class A HCC, usage of ICI is likely to be safe. 41,42 The treatment strategy for CPB HCC warrants further investigation. Here, we will describe the most common irAEs associated with ICCtreated HCC patients and discuss screening and monitoring strategies based on the general guidelines provided by SITC, ASCO, NCCN, and ESMO.…”
Section: Dovepressmentioning
confidence: 99%
“…OncoTargets and Therapy 2020:13 prognosis remains poor and the rate of irAEs always higher than patients with Child-Pugh class A HCC, usage of ICI is likely to be safe. 41,42 The treatment strategy for CPB HCC warrants further investigation. Here, we will describe the most common irAEs associated with ICCtreated HCC patients and discuss screening and monitoring strategies based on the general guidelines provided by SITC, ASCO, NCCN, and ESMO.…”
Section: Dovepressmentioning
confidence: 99%
“…describing real-world data on the efficacy and safety of immune checkpoint inhibitor (ICI) in advanced hepatocellular carcinoma (HCC) patients. 1 They found that the real-world performance of ICIs in advanced HCC appears comparable to that observed in clinical trials for HCC patients with Child-Pugh class A cirrhosis.…”
Section: Adverse Events Of Immune Checkpoint Inhibitors In Advanced H...mentioning
confidence: 82%
“…An observational study confirmed the safety and efficacy of nivolumab across various lines of therapy 49 . The use of immune checkpoint inhibitors (ICI) in advanced HCC has been shown to be a comparable to that in HCC patients with Child‐Pugh A cirrhosis 50 …”
Section: Systemic Treatment For Hccmentioning
confidence: 83%
“…49 The use of immune checkpoint inhibitors (ICI) in advanced HCC has been shown to be a comparable to that in HCC patients with Child-Pugh A cirrhosis. 50 Lenvatinib has been shown to be an effective second-line therapy in a number of real-world settings. 37,[51][52][53] TA B L E 1 Systemic therapies for the treatment of hepatocellular carcinoma a drug combination recently approved by the FDA, has been shown to markedly improve overall survival and progression-free survival compared to sorafenib, and real-world studies are expected.…”
Section: Sys Temi C Tre Atment For H Ccmentioning
confidence: 99%